Identification of Basic Fibroblast Growth Factor as the Dominant Protector of Laminar Shear Medium from the Modified Shear Device in Tumor Necrosis Factor-α Induced Endothelial Dysfunction - Wang, Huang-Joe; Lo, Wan-Yu (Frontiers in Physiology, 2018)
Background and Aims: Endothelial dysfunction is a hallmark of cardiovascular diseases. The straight region of an artery is protected from atherosclerosis via its laminar blood flow and high shear stress. This study investigated the cytoprotective effects of a new laminar shear medium (LSM) derived from a modified cone-and-plate shear device and identified basic fibroblast growth factor (bFGF) secreted by human aortic endothelial cells (HAECs) as the dominant protective factor in the LSM. Methods: Based on a modified cone-and-plate shear device system, HAECs were exposed to laminar shear (15 dynes/cm2) and static for 24 h to produce a new supernatant LSM and static medium (SM). Evaluation of the protective effects of LSM and SM on endothelial dysfunction induced by tumor necrosis factor (TNF)-α (10 ng/mL), which leads to production of reactive oxygen species (ROS), inflammatory monocyte adhesion, and tissue factor activity. ROS induction-, inflammation-, and thrombosis-related genes and protein expression were evaluated by quantitative-PCR and western blotting. To identify the cytokines that played a key role in the cytoprotective action of the LSM, we used cytokine antibody arrays, selected an abundant marker cytokine, bFGF, and validated the different cytoprotective effects of recombinant bFGF (rbFGF) and neutralization by monoclonal antibody (rbFGF+Ab) co-treatment. Aortic and lung tissues from different groups of C57BL/6J mice were examined by immunohistochemistry. SB203580 (specific inhibitor of p38) and BIX02189 (specific inhibitor of MEK5) were used to identify bFGF as the main cytoprotective factor acting via p38/MAPK and MEK5-KLF2 pathways. Results: Compared with traditional LSM, the new LSM not only significantly decreased TNF-α-induced intracellular adhesion molecule 1 and plasminogen activator inhibitor type 1 gene expression, but also significantly increased heme oxygenase 1 gene expression. The new LSM and bFGF attenuated TNF-α-induced ROS induction, inflammation, and tissue factor activity and inhibited the inflammatory- and thrombosis-related gene/protein overexpression both in vitro and in vivo. Mechanistically, the cytoprotective action of bFGF was mediated via the p38/MAPK and MEK5-KLF2 pathways. Conclusion: bFGF was identified as the critical factor mediating the cytoprotective effects of LSM derived from the modified laminar shear system.